Murine Cytomegalovirus–induced Complement-fixing Antibodies Deposit in Murine Renal Allografts During Acute Rejection. Issue 8 (20th July 2021) - Saunders, Ute; Li, Mao; Boddeda, Srinivasa R.; Maher, Sonya; Ghere, Jessica; Kaptsan, Irina; Dhital, Ravi; Velazquez, Victoria; Guo, Lingling; Chen, Bo; Zeng, Qiang; Schoeb, Trenton R.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Human cytomegalovirus (CMV) infection is associated with renal allograft dysfunction and loss, particularly in combination with acute rejection. Emerging literature suggests that non-HLA antibodies may contribute to antibody-mediated rejection, but pathogen-induced antibodies have not been investigated in this context. This study examines the presence of CMV-induced antibodies in murine CMV (MCMV)–infected renal allografts during acute rejection. Methods: Intragraft immunoglobulin G (IgG) and complement C3 immunostaining were compared among allogeneic MCMV D − /R −, D + /R −, and D + /R + renal transplants. Intragraft antibody deposition was examined in B cell–deficient recipients treated with MCMV immune sera. Antibody binding and complement-dependent cytotoxicity (CDC) of D − /R − and D + /R + sera against infected renal tubular epithelial cells (TECs) were measured in vitro. IgG immunostaining was performed in D + /R + allografts and native kidneys and in D + /R − allografts treated with ganciclovir to inhibit viral replication. Results: D + /R − and D + /R + transplants had more abundant IgG and C3 deposition compared with D − /R − recipients. Greater IgG deposition was associated with more severe allograft injury in B cell–deficient recipients treated with MCMV immune sera compared with nonimmune sera. D + /R + sera induced greater CDC of infected TECs compared with D − /R − sera. Native kidneys had lower IgG deposition compared with allografts, despite similar organ viral loads. Ganciclovir-treated allografts had reduced IgG deposition compared with untreated allografts. Conclusions: In this murine model, complement-fixing antibodies can deposit into MCMV-infected renal allografts, are associated with allograft damage, and can induce CDC of MCMV-infected renal TECs. The allogeneic response and viral replication may also contribute to intragraft antibody deposition.